Shrink-swell behavior of expansive clayey soils stabilized using fly ash-derived geopolymer - Francisco, Luigi Christian B.; Señagan, Rachelda D. (College of Engineering, University of the Philippines Diliman, 2018)
Expansive soils undergo significant shrinking and swelling when subjected to changing moisture conditions. This pose problems to structures and properties, especially on road pavements. The burning of coal for power generation produces substantial amounts of byproducts including fly ash, which end up in landfills and cause environmental hazards. The need for its utilization is necessary, in order to reduce its environmental impacts. In this study, fly ash-derived geopolymer was used to stabilize expansive clayey soils. Various mixes of the expansive soil stabilized using fly ash geopolymer were subjected to curing periods of 7, 14, and 21 days at room temperature, and the Free Swell Index (FSI) test and the Modified Free Swell Index (MFSI) test was conducted in order to assess the soil's expansiveness. To determine the effect of soil stabilization without geopolymerization, three control mixes were done, which substantially changed the high degree of expansiveness of the baseline soil bentonite mixture to moderate. Upon employing geopolymerization, the degree of expansiveness was all reduced to low. By performing statistical analysis, it was found out that that there is no significant difference on the MFSI obtained for different curing periods. Moreover, the effect of the variation of sodium hydroxide (NaOH) to the MFSI was investigated, and statistical analysis showed that the mix with 10% NaOH exhibited significantly lower means than those with 15% and 5% NaOH. Upon investigation of the effect of the variation of fly ash (FA) to the MFSI, statistical analysis showed that there is no significant difference among the values of their means. Hence, the mix with 40% FA and 10% NaOH proved to be the optimal mix among all that were tested. Furthermore, it could be concluded that fly ash-derived geopolymer is a viable method in stabilizing expansive soils